Pneumococcal endocarditis complicating meningitis and arthritis in a previously healthy woman: A case report. Issue 3 (March 2015) - Okada, Taiji; Yoshitomi, Hiroyuki; Harada, Yuji; Ito, Shimpei; Nakamura, Taku; Adachi, Tomoko; Nakashima, Ryuma; Sugamori, Takashi; Endo, Akihiro; Takahashi, Nobuyuki; Tanabe, Kazuaki
Abstract Streptococcus pneumoniae is the most common cause of community-acquired bacterial meningitis in adults. Pneumococcal endocarditis coexisting with meningitis is rare, especially in healthy individuals. A 66-year-old woman was admitted with pneumococcal bacteremia, meningitis, and arthritis. She was in good condition before admission. Because of typical presentation of bacterial meningitis characteristics and normal echocardiographic findings, the patient was administered antibiotics for meningitis and arthritis. On hospitalization day 59, she developed a fever, and echocardiography showed severe aortic regurgitation, perforation, and vegetation of the aortic valve. She was diagnosed with pneumococcal endocarditis and underwent aortic valve replacement surgery. In general, invasive pneumococcal infections occur in debilitated middle-aged men with predisposing factors such as chronic alcoholism, chronic obstructive pulmonary disease, and immunosuppressive conditions. In this case, regardless of the appropriate treatment and no risk of invasive pneumococcal infections, infective endocarditis occurred. <Learning objective: This case suggested that invasive pneumococcal infections progressing to infective endocarditis can occur in healthy individuals and underscore the importance of careful observation in patients with pneumococcal meningitis, in particular, in the case of blood culture positive patients.>